MY SAY: What is life without 'potong'? - Abd Razak, Dzulkifli (2009)
When I was little, one of the joys of life was to wait for the ice cream "potong" man. Things were so simple that it was a thrill to just pick from the variety of flavours, including my alltime favourite durian. I can still picture the rectangular ice cream "potong" stuck on a rounded bamboo stick that brought so much happiness to children those days. It cost 10 sen for the whole piece and five for half. For loyal customers, it was possible to get two different flavours in each half with no increase in cost. This, of course, was the preserve of a few.